Radiation Dose Reduction as an Objective Marker of Procedural Maturation During Early Neurointerventional Fellowship Training: A Six-Month Longitudinal Study - Pinto Desti Ramadhoni; Lenny Octavinawaty; Diah Andini; Budiman Juniwijaya; Natasya Wanda Yuniza; Nurdiansyah Nurdiansyah; Dewie Susan; Ardy Oktaviandi (Journal of Neurointervention and Stroke, 2026)
Highlight: Radiation dose declined progressively during early neurointerventional training Radiation dose has a clearer temporal trend than fluoroscopy time in early training ABSTRACT Introduction: Radiation safety is a fundamental component of neurointerventional practice and competency-based fellowship training. While fluoroscopy time has traditionally been used as a surrogate marker of procedural efficiency, it may not accurately reflect total radiation exposure. Dose-related metrics may better represent technical maturation and radiation-conscious procedural behavior during fellowship progression. Objective: This study compared fluoroscopy time and radiation dose to characterize the early learning curve of neurointerventional fellowship training. Method: This retrospective observational study analyzed 108 consecutive DSA-based brain angiograms performed during the first six months of a supervised fellowship. Chronological case-sequence linear regression was employed to evaluate longitudinal changes in radiation dose and fluoroscopy time. Result: The mean fluoroscopic radiation dose decreased by 42.8%, dropping from 170.17 mGy in month 1 to 97.36 mGy in month 6. Linear regression revealed a significant negative association between case sequence and radiation dose (B = -0.468 mGy/case; p = 0.012; R2 = 0.058). In contrast, fluoroscopy time showed only modest fluctuations and no significant linear association (p = 0.780). Conclusion: During early fellowship training, fluoroscopic radiation dose demonstrates a clearer temporal trend than fluoroscopy time, suggesting it is a more informative marker of procedural maturation. However, the low explanatory power and the absence of adjustment for procedural complexity require cautious interpretation. These findings warrant further research incorporating complexity-adjusted designs to better define technical maturation.